Differential methylation in inflammation and type 2 diabetes genes in siblings born before and after maternal bariatric surgery. (6th December 2015) - Berglind, Daniel; Müller, Patrick; Willmer, Mikaela; Sinha, Indranil; Tynelius, Per; Näslund, Erik; Dahlman‐Wright, Karin; Rasmussen, Finn
Abstract : Objective: Siblings born before (BMS) and after (AMS) maternal biliopancreatic diversion (BPD) show differences in the methylome. The objective was to use a sibling‐pair design to examine the effects from interpregnancy weight loss as a consequence of maternal bariatric surgery, other than BPD, on the methylome comparing BMS and AMS. Methods: Women with at least one child born before and one after bariatric surgery were identified in Swedish national registers. Whole blood samples from BMS ( N  = 31) and AMS ( N  = 31) siblings were collected for epigenetic methylation analysis while maternal information was collected from antenatal medical records. Results: In total 3, 074 genes, with corresponding 23, 449 CpG methylation sites, were differently methylated and associated with an overrepresentation of differently methylated CpG sites in genes involved with insulin receptor signaling, type 2 diabetes signaling, and leptin signaling in obesity, while the most significant differently methylated genes were HLA‐DQA1, HLA‐DQB1, and TSPAN18, when comparing BMS and AMS siblings. Conclusions: These results suggest that maternal bariatric surgery, with subsequent weight loss between pregnancies, is associated with alterations in the methylome of genes involved in insulin receptor signaling, type 2 diabetes signaling, and leptin signaling in obesity in a comparison of BMS and AMS siblings.